The Importance of Organizational Innovation and Adaptation in Building Academic–Industry–Intelligence Collaboration: Observations from the Laboratory for Analytic Sciences. Issue 3 (2nd September 2017) - Vogel, Kathleen M.; Jameson, Jessica Katz; Tyler, Beverly B.; Joines, Sharon; Evans, Brian M.; Rendon, Hector
ABSTRACT: This article discusses the establishment and development of the Laboratory for Analytic Sciences (LAS), a unique site of academic–industry–intelligence collaboration, established in 2013 by the National Security Agency (NSA) and located on the campus of North Carolina State University. Since 2014, the authors have been participant-observers of LAS research teams. This article describes how inter-institutional, interdisciplinary collaboration has developed at LAS, drawing on multi-year data involving observations, surveys, and interviews that the authors have collected. LAS provides an opportunity to study the operationalization of an academic–intelligence collaboration and gather lessons learned in order to inform future collaborative efforts by the U.S. intelligence community. What this article reveals is the importance of organizational innovation and adaptation in light of various challenges that emerge in inter-institutional and interdisciplinary collaboration.